VIth World Congress on Science and Football, Book of Abstracts, January 16-20, 2007, Antalya, Turkey - Poster Presentations - Fitness Assessment (Journal of Sports Science & Medicine, 2007)
Summaries on the following topics: P-090 Dynamic balance and posture in visually impaired soccer players P-091 Motion skills on soft sand and conventional surface in beach soccer P-092 Seasonal changes in aerobic fitness of circumpubertal football players P-093 Changes in fitness variables of professional Brazilian soccer players in preseason P-094 Follow-up of the training process of a macedonian first league professional soccer team with heart rate and blood lactate monitoring P-095 Effects of concentrated charges of strength training on anaerobic variables and body composition of professional soccer players P-096 The effect of sprint exercises on serum superoxide dismutase, catalase and malondialdehyde levels in soccer players P-097 Methodic of speed endurance development by professional soccer players